Disability, Subject‐Dependence, and the Bad‐Difference View. - Ishida, Shu; Sasaki‐Honda, Mitsuru; Sawai, Tsutomu (Bioethics, 2025)
Philosophers have debated on the "mere‐difference" view of disability, according to which disability as such is neutral in terms of well‐being, just like race and gender. It is contrasted with the "bad‐difference" view, which holds that disability is bad for its possessor even in a non‐ableist situation. We first illustrate how neither view can be sensitive to the diversity of disabled people and their disabilities. Subsequently, we propose an alternative outlook—the conditional bad‐difference view of disability: a disability is bad for its possessor if and only if it hampers her aspired way of life, even without ableism. In addition to being theoretically moderate and thus more plausible than the existing outlooks, this view also offers a robust ethical case for policies and practices catering to the varying needs and values of disabled people, such as personalized healthcare and the user‐led research of assistive technologies.